Tribological Evaluation of Lead-Free MoS2-Based Solid Film Lubricants as Environmentally Friendly Replacements for Aerospace Applications - Parikshit Tonge; Amit Roy; Payank Patel; Charles J. Beall; Pantcho Stoyanov (Lubricants, 2022)
Solid lubricants, such as MoS2 have been widely used in the aerospace industry with the primary purpose of reducing the friction and wear of tribological interfaces. MoS2 based solid film lubricants are generally doped with other compounds, which can help overcome some of their limitations related to environmental conditions. For instance, compounds like Sb2O3 and Pb have been traditionally used to improve the endurance life of these lubricants. However, with the recent zest in transferring to eco-friendly lubricants, there is a strong push to eliminate Pb based compounds. The main purpose of this work is to better understand the influence of Pb based compounds on the tribological behavior of MoS2 based solid film lubricants as well as to critically evaluate the performance of Pb free lubrication strategies. More specifically, the baseline ‘non-green’ lubricant was doped with Pb compound and Sb2O3 and the Pb compound in the ‘Green’ alternative lubricant was replaced by more Sb2O3. The wear test was done using a ball-on-disk tribometer for specific loads and for 5000 cycles. Ex-situ analysis was conducted using Scanning Electron Microscope (SEM), Atomic Force Microscopy (AFM), and micro-Raman to capture the interfacial processes of these lubricants at different loads. Overall, the non-green lubricant performed better in terms of the tribological behavior (i.e., lower friction and wear), which was attributed to the formation of a dense MoS2-based tribo-/transfer-film with the basal planes oriented in the parallel direction to the sliding. The finding on the interfacial phenomena provided critical insights into the development of novel green alternatives that may have the ability to replace Pb based compounds in the future for a sustainable environment.